Urdu Ghazal in Azad Kashmir - Muhammad Saghher Khan; Sardar Asghar Iqbal (بازیافت)
The study deals with the status of Ghazal, the most popular genre of Urdu poetry in subcontinent-in post 1947 era in AZAD KASHMIR. In fact this part of Kashmir has no known literary tradition in terms of the evolution and growth of Urdu Ghazals. However, in the post partition epoch, it has nurtured and developed significant poetic works chiefly in the arena of Ghazals because of close proximity with rich traditions in the main stream literary movements around especially progressive and traditional school of thoughts .on the top of this, this land has germinated and groomed such a high class of poets who have produced poetic works of par excellence. Among the scores of poets, the researcher has selected almost thirty poets whose works are significant. The account and analysis of their works is introductory and analytical .It is to describe that this study is pioneering in nature and hopefully be beneficial to critics, literary students, common readers and researchers.